Molecular characterization and Antibiotic resistance profiles of Escherichia coli extended-spectrum Î²-lactamases producer strains isolated from urine samples in Benin - Mousse, Wassiyath; Sina, Haziz; Wele, Mamadou; Chabi, Nicodeme; Nouvlessounon, Durand Dah; Bade, Farid T.; Chabi, Faridath; Anagonou, Severin; Adjanohoun, Adolphe; Baba-Moussa, Lamine (European Scientific Journal, ESJ, 2018)
Urinary tract infections are the second common reason of medical consultations and antibiotics prescription. Escherichia coli is known to cause most urinary tract infections. The aim of this study was to characterize and determine the antibiotic resistance profile of E. coli extended-spectrum Î²lactamases (ESBL) producer strains isolated from urine samples. The urine samples collected came from hospitalized and non-hospitalized patient referred to Hubert Koutoukou Manga (HKM), National and University Hospital Center (Cotonou, Benin). The resistance to antibiotics was determined according to the disk diffusion method. The production of penicillinase and ESBLs was researched respectively by the acidimetric test and double disk synergy method. The presences of genes encoding Î²lactamases were detected by Polymerase Chain Reaction (PCR). Our data revealed that 60 % of E. coli strains (101) were isolated from female patients. Also, 69.31 % of the strains were isolated from non-hospitalized patients. The high resistance levels were recorded with amoxicillin (96.04 %) and amoxicillin + clavulanic acid (66.34 %). Twenty percent (20%) of strains were ESBLs. Among ESBLs strains, 70% comes from non-hospitalized patients. Eighty percent of E. coli strains produced penicillinase among which 25 % were ESBL producers. All the ESBL producers strains carried blaTEM gene whereas only 30 % carried the blaSHV gene. This study updates the data on the prevalence to antibiotic resistance of E. coli ESBL producers strains for better management of urinary tract infections.